Ensino, ofício e prática cirúrgica na obra de Henri de Mondeville: cirurgiões na corte francesa e nos campos de batalha (séculos XIII-XIV) - Damaceno, Mauricio Ribeiro (2020)
This dissertation is guided by the French physicist-surgeon Henri de Mondeville, his academic trajectory, training and teaching and his performance at the court of Filipe IV, Belo. The main source is and his unfinished work The Surgery, in which he discusses, based on the ancient authorities, Galen and Arabs, Avicenna, on the surgical and therapeutic precepts in the case of war injuries. His training in the field of medicine and surgery and his teaching activities as a master took place in the General Studies of Paris, Montpellier and Bologna. In the latter he did an internship with the famous surgeon Teodorico Borgognoni. Regarding the profession, it can be noted that a number of skills were necessary to be a good surgeon, among them were intellectual skills (knowing the canons and prescriptions for medicines), physical (having strong limbs and thin fingers) and functional (not fear the bad smell, be goodwill, have quick ingenuity). Anatomy was one of the important skills, but it came up against the symbolism that involved the body in the Middle Ages. Finally, in practice, the physical-surgeon could act in the different segments of society, but the place that could give him greater prestige was certainly the court. King Philip IV, O Belo, following a common pattern in the Capetíngia dynasty, recruited at least 20 physicists and surgeons during his reign, especially in times of war with the Flemish. In the battle, the health professional put everything he learned into execution, especially regarding injuries caused by weapons such as arrows and swords. The presence of surgeons and physicists renewed the hopes of those who were wounded in combat.